Hal, a Prompt - Carmen Olivares Rivera (Miscelánea: A Journal of English and American Studies)
Hal is the governing computer in the spaceship Discovery which appears in Clarke -Kubrick's 2001: A Space Odyssey. Hal has the shape and structure of an artifact although it/he exhibits signs of human-like behavior. The computer confronts us with several issues that consistently strike our minds such as the notion of intelligence, mental disorder and moral responsibility. The paper explores Hal's conduct from a psychological and moral perspective stressing his status as an actual character in the story.